Concepts and Molecular Aspects in the Polypharmacology of PARP‐1 Inhibitors. (1st October 2015) - Passeri, Daniela; Camaioni, Emidio; Liscio, Paride; Sabbatini, Paola; Ferri, Martina; Carotti, Andrea; Giacchè, Nicola; Pellicciari, Roberto; Gioiello, Antimo; Macchiarulo, Antonio
Abstract: Recent years have witnessed a renewed interest in PARP‐1 inhibitors as promising anticancer agents with multifaceted functions. Particularly exciting developments include the approval of olaparib (Lynparza) for the treatment of refractory ovarian cancer in patients with BRCA1/2 mutations, and the increasing understanding of the polypharmacology of PARP‐1 inhibitors. The aim of this review article is to provide the reader with a comprehensive overview of the distinct levels of the polypharmacology of PARP‐1 inhibitors, including 1) inter‐family polypharmacology, 2) intra‐family polypharmacology, and 3) multi‐signaling polypharmacology. Progress made in gaining insight into the molecular basis of these multiple target‐independent and target‐dependent activities of PARP‐1 inhibitors are discussed, with an outlook on the potential impact that a better understanding of polypharmacology may have in aiding the explanation as to why some drug candidates work better than others in clinical settings, albeit acting on the same target with similar inhibitory potency. Abstract : Right on PAR : The increased understanding of molecular aspects in the polypharmacology of PARP‐1 inhibitors is driving the development of these compounds toward novel cancer therapies. It provides an explanation for the varied sensitivity or resistance of cancer cells toward certain compounds, and clues as to why some drug candidates work better than others in clinical settings. Herein we provide an overview of the distinct levels of the polypharmacology of PARP‐1 inhibitors, including inter‐family, intra‐family, and multi‐signaling polypharmacology.